2014
DOI: 10.17221/7338-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed supplementation with manganese from its different sources on performance and egg parameters of laying hens

Abstract: ABSTRACT:The objective of this study was to compare the effects of feed supplementation of laying hens with manganese from its inorganic and organic sources on performance and some parameters of egg quality. Ninety-six hens at 20 weeks of age were randomly allocated to 4 dietary treatments, each consisting of 6 replicates (4 birds per replicate). The control group was fed unsupplemented basal diet (BD) with only natural background Mn level of 46.4 mg/kg feed. For the three experimental treatments, the BD was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
5
14
3
1
Order By: Relevance
“…Similarly to Świątkiewicz and Koreleski (2008), Venglovská et al (2014), Xiao et al (2014Xiao et al ( , 2015, Mabe et al (2003), and Stefanello et al (2014), who studied different sources of trace minerals, we can affirm that minerals in the form of CAPC improve not only the strength, but also the shell thickness, egg component weights, and albumen quality.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly to Świątkiewicz and Koreleski (2008), Venglovská et al (2014), Xiao et al (2014Xiao et al ( , 2015, Mabe et al (2003), and Stefanello et al (2014), who studied different sources of trace minerals, we can affirm that minerals in the form of CAPC improve not only the strength, but also the shell thickness, egg component weights, and albumen quality.…”
Section: Discussionsupporting
confidence: 71%
“…Venglovska et al (2014) observed beneficial effects of Mn, especially from organic sources, on eggshell quality. The importance of minerals is related to changes of the arrangement pattern of shell membrane fibres in relation to the structural composition of eggshell.…”
Section: Introductionmentioning
confidence: 86%
“…The National Research Council (1994) estimated the requirement for Ca, non-phytate phosphorus (NPP), and Mg at 110 g of feed per brown-egg layer daily as 3.6 g, 0.275 g, and 0.055 g, respectively. Dietary Mg concentration has been associated with laying performance and eggshell quality (Stafford and Edwards 1973;Ding and Shen 1992;Venglovska et al 2014). Previous experiments indicated that the eggshell strength improved in laying hens when the Mg concentration in their diet was increased above the Mg nutrition requirement (Atteh and Leeson 1983a, b;Hess and Britton 1997;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%